DAMPAK EMOSI POSITIF TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN DAN DAYA TARIK PENGECER STUDI EMPIRIK PADA LOTTE MART KELAPA GADING JAKARTA UTARA - Dergibson Siagian (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2015)
The phenomenon of the proliferation of retail outlets in Indonesia is not surprising anymore. This phenomenon happens because the fulfillment of daily needs is so important and also there is a shift in people habit from spending in traditional markets to modern markets. Lotte Mart uses this phenomenon to continue to compete with other retail outlets in Indonesia. This research aimed to find out the influence of positive affect to customer loyalty through satisfaction with the retailer and retailer interest in Lotte Mart Kelapa Gading, North Jakarta. The theory used to support this research was positive affect, satisfaction with the retailer, retailer interest, and customer loyalty. This study used a questionnaire for data collection and non-probability sampling with judgment sampling technique. The procedure used to test the model and data processing was structural equation model (Structural Equation Modelling) using WarpPLS 4.0. The conclusion from this study was all hypotheses has been proven to have a positive and significant influence either directly or indirectly.Â Keywords: Emotion, Satisfaction, Retailer, Â Interest, and Â Loyalty.